PERANAN IBU RUMAH TANGGA DALAM PENINGKATAN EKONOMI KELUARGA MELALUI SEKTOR UMKM DI DESA PAGAR DEWA KABUPATEN BENGKULU SELATAN PROVINSI BENGKULU - Nurjanah, Indah Putri; Mayasari, Mayasari (Universitas Batanghari Jambi, 2019)
Abstract This study aims to find out how to increase household income through MSMEs and the role of housewives in improving the family economy in Pagar Dewa Village, South Bengkulu Regency. The design of this study uses descriptive qualitative. Meanwhile, the technique in this study uses a purposive technique, namely the determination of informants is not based on guidelines or based on population representatives, but based on the depth of information needed, namely by finding key informants who will then proceed with other informants with the aim of developing and seeking as much information as possible. related to research problems. The results showed that (1) through MSMEs carried out by housewives in Pagar Dewa Village can increase income for families, because the income generated can meet more decent needs such as meeting the needs of clothing, food and shelter. (2) Housewives in the village of Pagar Dewa is very instrumental in improving the family's economy, because of the desire of a mother who wants to help ease the cost and burden of family life given the increasing needs of life so that this housewife works through the MSME sector in order to earn money and add income to her husband. Keywords : The Role of Housewives, Family Economy and SMEs